1981 Biennial Exhibition. - 1981 Biennial Exhibition (New York : Whitney Museum of American Art, 1981)
Acconci, Vito ; Adams, Robert ; Amenoff, Gregory ; Anastasi, William ; Anger, Kenneth ; Armajani, Siah ; Arnoldi, Charles ; Aycock, Alice ; Bailey, William ; Bartlett, Jennifer ; Benglis, Lynda ; Benning, James ; Borofsky, Jonathan ; Brakhage, Stan ; Breer, Robert ; Brewster, Michael ; Buckner, Barbara ; Burton, Scott ; Callahan, Harry ; Callis, Jo Ann ; Chase, Louisa ; etc.
1981 Biennial Exhibition, Whitney Museum of American Art, New York, Fourth floor: January 20 - April 5, 1981 ; Third floor: January 27 - April 19, 1981 ; Second floor: February 4 - April 12, 1981 ; Films, second floor Film/Video Gallery: February 4 - April 12, 1981 ; Video, second floor back gallery: February 4 - April 12, 1981
boek